Effect of resistance training frequency on gains in muscular strength: A systematic review and meta-analysis - Grgic, J.; Schoenfeld, B. J.; Davies, T. B.; Lazinica, B.; Krieger, J. W.; Pedisi, Z. (Sports Medicine, 2018)
Current recommendations on resistance training (RT) frequency for gains in muscular strength are based on extrapolations from limited evidence on the topic, and thus their practical applicability remains questionable. Objective: To elucidate this issue, we conducted a systematic review and meta-analysis of the studies that compared muscular strength outcomes with different RT frequencies. Methods: To carry out this review, English-language literature searches of the PubMed/MEDLINE, Scopus, and SPORTDiscus databases were conducted. The meta-analysis was performed using a random-effects model. The meta-analysis models were generated with RT frequencies classified as a categorical variable as either 1, 2, 3, or 4+ times/week, or, if there were insufficient data in subgroup analyses, the training frequencies were categorized as 1, 2, or 3 times/week. Subgroup analyses were performed for potential moderators, including (1) training volume; (2) exercise selection for the 1 repetition maximum (RM) test (for both multi-joint and single-joint exercises); (3) upper and lower body strength gains; (4) training to muscular failure (for studies involving and not involving training to muscular failure); (5) age (for both middle-aged/older adults and young adults); and (6) sex (for men and for women). The methodological quality of studies was appraised using the modified Downs and Black checklist. Results: A total of 22 studies were found to meet the inclusion criteria. The average score on the Downs and Black checklist was 18 (range 13-22 points). Four studies were classified as being of good methodological quality, while the rest were classified as being of moderate methodological quality. Results of the meta-analysis showed a significant effect (p = 0.003) of RT frequency on muscular strength gains. Effect sizes increased in magnitude from 0.74, 0.82, 0.93, and 1.08 for training 1, 2, 3, and 4+ times per week, respectively. A subgroup analysis of volume-equated studies showed no significant effect (p = 0.421) of RT frequency on muscular strength gains. The subgroup analysis for exercise selection for the 1RM test suggested a significant effect of RT frequency on multi-joint (p < 0.001), but not single-joint, 1RM test results (p = 0.324). The subgroup analysis for upper and lower body showed a significant effect of frequency (p = 0.004) for upper body, but not lower body, strength gains (p = 0.070). In the subgroup analysis for studies in which the training was and was not carried out to muscular failure, no significant effect of RT frequency was found. The subgroup analysis for the age groups suggested a significant effect of training frequency among young adults (p = 0.024), but not among middle-aged and older adults (p = 0.093). Finally, the subgroup analysis for sex indicated a significant effect of RT frequency on strength gains in women (p = 0.030), but not men (p = 0.190). Conclusions: The results of the present systematic review and meta-analysis suggest a significant effect of RT frequency as higher training frequencies are translated into greater muscular strength gains. However, these effects seem to be primarily driven by training volume because when the volume is equated, there was no significant effect of RT frequency on muscular strength gains. Thus, from a practical standpoint, greater training frequencies can be used for additional RT volume, which is then likely to result in greater muscular strength gains. However, it remains unclear whether RT frequency on its own has significant effects on strength gain. It seems that higher RT frequencies result in greater gains in muscular strength on multi-joint exercises in the upper body and in women, and, finally, in contrast to older adults, young individuals seem to respond more positively to greater RT frequencies. More evidence among resistance-trained individuals is needed as most of the current studies were performed in untrained participants.